Pengaruh Work Life Balance dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai Pada Salah Satu UPT TPA Wilayah Sukabumi - Mardiahtun Nisa; Mochamad Vrans Romi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Job satisfaction is important in supporting productivity at UPT TPA Sukabumi. Employees who feel happy tend to be more motivated and loyal. Based on various studies, the main factor influencing job satisfaction is the harmonization between career demands and individual life (work-life balance). However, non ASN employees face obstacles such as uncertain job status, lack of facilities, uneven division of work time, and poor communication. This study analyzes how much effect work-life balance and workplace environment have on job satisfaction of non-ASN employees through a quantitative approach. Data analysis was conducted by analyzing multiple regression supported using SPSS. Data was obtained from 33 non-ASN employees by conducting observations, interviews, and distributing questionnaires, using a semantic differential scale. The results of the study indicate that both separately and simultaneously, work life balance and work environment have a positive and significant influence on job satisfaction of employees. That is, when the balance between personal life and work is achieved and the work environment conditions are supportive, the level of employee job satisfaction will also increase significantly.